Shear bond strength evaluation of adhesive and tooth preparation combinations used in reattachment of fractured teeth: An ex-vivo study - Ramachandruni VamsiKrishna; Koppolu Madhusudhana; Aluru Swaroopkumarreddy; Anumula Lavanya; Chinni Suneelkumar; Govula Kiranmayi (Wolters Kluwer Medknow Publications, 2015)
Objectives: The objectives of this study were to evaluate the bond strengths of different adhesive materials, different tooth preparation designs and adhesive tooth preparation combinations to reattach fractured incisor fragments. Materials and Methods: The study sample comprised 48 intact human maxillary central incisors divided into two groups A and B. The incisal third was sectioned with a diamond disc. The teeth in Group A were reattached with bonding agent and in Group B with resin luting cement. The teeth in each Group were further divided into three sub-groups based on the preparation designs viz., simple attachment, chamfer on labial surface, groove with shoulder on labial surface and restored with nano-composite. Shear Bond Strength was calculated by applying load incisal to the fracture line. T-test and one-way ANOVA were used to evaluate the bond strength between the groups and within the group respectively. Results: Reattachment with resin luting cement showed high bond strength compared to bonding agent (P < 0.05). Within the subgroups 'groove with shoulder' showed better bond strength compared to simple attachment and chamfer and the result was statistically significant (P < 0.05).Conclusion: Reattachment of fractured fragments can be considered as a good alternative treatment option when the fragment is available.Reattachment with resin luting cement and the preparation design of "groove with shoulder" showed better results.